Предмет: Алгебра, автор: Аноним

cos^2x-3sin^2x=-sin2x

Ответы

Автор ответа: wangross
0
cos^2x-3sin^2x=-sin2x  \cos^2x-3sin^2x+sin2x=0 \ cos^2x-3sin^2x+2sinxcosx=0|:cos^2x neq 0;~~~x neq  frac{ pi }{2} + pi k  \ 1-3tg^2x+2tgx=0|*(-1) \ 3tg^2x-2tgx-1=0 \ D=4-4*3*(-1)=4+12=16 \ tgx_1= frac{2+4}{6}= frac{6}{6} =1 ~~~~~~~~~~~~~~~~~~~~~~~~~~tgx_2=frac{2-4}{6}= frac{-2}{6} =- frac{1}{3} \ x_1= frac{ pi }{4}+ pi k~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~x_2=-arctg frac{1}{3} + pi k

Ответ:  frac{ pi }{4}+ pi k;~-arctg frac{1}{3} + pi k
Похожие вопросы